LEGAL BASIS AND IMPLICATIONS OF LAW NO. 20 OF 2003 ON THE EDUCATION SYSTEM IN INDONESIA - Agus Supriyanto; Gunawan Widjaja (International Journal of Teaching and Learning, 2025)
This study aims to analyse the legal basis and implications of Law No. 20 of 2003 on the National Education System for the implementation of education in Indonesia. The method used is a literature review with a descriptive analytical approach to various literature, legal documents, and related research results. The results of the study show that Law No. 20 of 2003 has a strong philosophical, juridical, and sociological basis, which serves as a normative foundation for building an inclusive, high-quality, and equitable national education system. The implications of this law are evident in significant changes in curriculum structure, equal access to education, financing, educator competence, and community participation in education. However, the implementation of this law faces challenges in the form of resource inequality and policy adaptation at the regional level. This study recommends synergy among stakeholders as the key to the successful implementation of the law for the development of a sustainable national education system.